Landscape empowerment a participatory design approach to create restorative environments for assembly line workers in the Foxconn Factory - Jiang, Bin (Singapore Springer, 2021)
This book discusses essential strategies and approaches to creating mentally restorative environments for highly stressed and depressed workers at sweatshop factories. Drawing on the Foxconn factory in Longhua, China and an adjacent urban village as a sample site for research and design practice, the book employs a bottom-up and participatory process. The content is divided into two main parts, the first of which investigates economic, cultural, human rights, and environmental issues related to the electronic industry and urban village, providing in-depth research on various aspects, especially the working and living conditions for Foxconn workers. Based on these findings, the second part highlights potential landscape designs to address a range of issues, locations, and scales. The book’s goals are to provide a set of original methods for research and design practice in a complex social and economic context, and to raise awareness regarding the health, dignity and freedom of millions of workers.
Electronic reproduction
Keywords: Factories -- Landscape architecture -- China; Architecture, Industrial -- China